Efficacy of McConnell’s Medial Patellar Taping Application for Pain Management and Walking Velocity of Osteoarthritis Patients - Wahju Hidajati1,; Angela BM Tulaar; Yoga Iwanoff Kasjmir; Sumariyono; Surjanto M.A (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: to evaluate the efficacy of medial patellar taping in addition to exercise for pain relief and 15 meters walking time, and to find any correlation between the pain improvement and functional outcome.Methods: This study was a randomized controlled trial of knee patellar taping in combination with the isometric and stretching exercise in comparison to taping free- exercise. The inclusion criteria includesknee osteoarthritis patients with VAS score ranges four to eight of each knee, with or without tolerable pain on the other knee. The treatment group received knee tapping and isometric and stretching exercise of thequadriceps, iliotibial band, hamstring and gastrocnemius muscles. Both treatment and control group were assessed for about three weeks (day 1/week 0, day 2, day 28/week 4, and day 49/week 7). A visual analoguescale (VAS) was used to assess knee pain severity whereas 15 m walking time assessed to measure functional gait performance. On day 2, both measurements were done for study group only, with assumption the resultwould be the same with 1 day exercise only. A Lequesne index measured functional outcome.Results: There were 24 participants, twelve patients were in the tapped group while the remaining twelve were in the control group. Significant pain differences were visible during the treatment period at day 1, day2 and at the beginning of week 7. At day 2 and week 4, the study group showed significant pain reduction in comparison to the control group (p < 0.007).The walking time also showed significant improvement in the study group at day 2 (p < 0.000) but there were no significant difference at week 4 and week 7. At week 7, the study group experienced pain (p < 0.037) andoutcome improvement significantly. In addition, for about 75% of them had none to moderate disability post intervention. Meanwhile, from the total of eight patients in the control group who had severe to very severedisability, four of them had moderate (50%) and the rest had mild disability (50%). There was significant correlation between the pain and functional outcome on day two.Conclusions: Medial Patellar Taping in addition to isometric and stretching exercise of quadriceps, iliotibial band, hamstrings and gastrocnemius muscles showed significant improvement of disability superior to theuntapped group. Benefits of Medial Patellar Taping remained three weeks after removal.Keywords: Osteoarthritis, Knee Pain Severity, exercise, Medial Patellar Taping, Visual Analogue Scale, 15 Meter Walking Time, Functional Gait Performance, Lequesne Index.